Investigating the impact of psychedelic drugs on social cognition defects: A scoping review protocol. - Sarah Ann Smith; Shaina Smith; Liz Dennett; Yanbo Zhang (PLoS ONE)
Background Impairments in social cognition are known to be a key factor in several psychiatric and neurodevelopmental disorders. Interest in psychedelic drugs has increased in recent years, with significant research identifying psychedelic and hallucinogenic drugs as modulators of social cognition. However, more research is necessary before psychedelics are implemented in clinical settings as treatments for social cognition defects. Therefore, this study describes a scoping review protocol which will be used to analyze the body of literature on psychedelic drugs as modulators of social cognition in patients with psychiatric and neurodevelopmental disorders. Methods This scoping review protocol was developed using the JBI Scoping Review Methodology Group's description of how to conduct a scoping review. The guidelines identified by this group as well as a search strategy developed with the assistance of a research librarian will be applied to a search of several peer-reviewed journals, including MEDLINE (Ovid), PsycINFO, EMBASE (Elsevier), and Scopus (Elsevier). Each study extracted will be screened in a two-step screening process, including a title and abstract screen, and a full-text screen. One independent individual will complete both steps of the screening, and a second independent individual will review the completed screening. Discussion An understanding of the current literature on psychedelic drugs as modulators of social cognition will provide insight into what is presently known on the subject, and any gaps in the literature that can be addressed in future studies. The knowledge gained from this scoping review could lead to a new treatment for social cognition defects in clinical populations.